2006
DOI: 10.2166/wst.2006.452
|View full text |Cite
|
Sign up to set email alerts
|

UV disinfection of wastewater effluents for unrestricted irrigation

Abstract: Wastewater reuse in arid regions is important for the production of a water resource to be utilised for non-potable purposes and to prevent the environmental transmission of disease-causing agents. This study was conducted to evaluate the effect of water quality on the comparative disinfection efficiency of viruses, bacteria and spores by UV irradiation. Furthermore, the microbial quality of effluent produced by coagulation, high rate filtration (HRF) and either UV irradiation or chlorination was determined. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…chloro-organic compounds) (Sun et al 2009;Zhang et al 2on), suggesting a search for a safer disinfection method is in place. UV disinfection is well established for effluent treatment in large WWTPs (Nasser et al 2006), but its use with CW effluent is much less established (Richter & Weaver 2003). Here we demonstrate the use of combined CW system and cheap, consumer level, UV disinfection systems to treat wastewater effluents, making it suitable for unrestricted irrigation.…”
Section: Introductionmentioning
confidence: 82%
“…chloro-organic compounds) (Sun et al 2009;Zhang et al 2on), suggesting a search for a safer disinfection method is in place. UV disinfection is well established for effluent treatment in large WWTPs (Nasser et al 2006), but its use with CW effluent is much less established (Richter & Weaver 2003). Here we demonstrate the use of combined CW system and cheap, consumer level, UV disinfection systems to treat wastewater effluents, making it suitable for unrestricted irrigation.…”
Section: Introductionmentioning
confidence: 82%
“…The effectiveness of a UV disinfection system depends on the characteristics of the effluents including the concentration of the sewage effluent, the intensity of the UV radiation and the time of the treatment (Kollu and Ormeci 2012). Nasser et al (2006) revealed that the treated sewage disinfected by UV is suitable for the unrestricted irrigation of food crops (FC < 1000 CFU/100 mL). Dungeni et al (2010) suggested UV disinfection as an additional treatment process of effluents to increase the effective inactivation and removal of pathogenic bacteria and viruses.…”
Section: Uv Irradiationmentioning
confidence: 99%
“…Rapid sand filtration is considered, with the bacl<:wash water discharged to the WWTP. • Disinfection to achieve the required level of pathogen removal to allow unrestricted reuse of effluent (Chrtek & Popp 1991;Nasser et al 2006;Oparaku et al 2on). A faecal coliform standard of 200 MPN/100 ml is to be achieved by UV lamps.…”
Section: Required Additional Effluent Treatmentmentioning
confidence: 99%